Tax Effects on the Value of Incentive Stock Options (ISOs) and the Decision to Go Public - Thomas A. Rhee (Journal of Small Business Finance, 1991)
The incentive stock options (ISOs) are similar to the regular stock call options. However, when one considers various taxing laws regarding the ISO stocks, the ISOs have unique features differentiated from the regular stock call options. In general, no income from ISOs is realized, for tax purposes, either upon the grant or exercise of the ISOs, until the ISO stock is actually sold. This poses an interesting question to executives with ISOs about when the firm should go public. In fact, a significant wealth can accrue to executives with the ISO stocks, when the firm's stock becomes publicly traded. Therefore, any changes in the tax law may affect the financial value of ISOs and also the firm's decision to go public. The present paper examines the valuation process of the ISOs and investigates the economic effects of tax law changes on “going public.” The result suggests that the 1986 TRA may have delayed the firm's decision to go public, while the U.S. Administration's recent individual income tax hike to finance the government deficit may somewhat encourage the firm's activity to go public.
Keywords: G32; G12; M52; 650; Incentives; Stock Options; Stocks; Tax Effects; ISO; IPO